Leadership Development in Ophthalmology: Investing In the Future of the Profession - Green, Catherine (Pakistan Journal of Ophthalmology, 2017)
Over the last two decades, there has been widespread acknowledgement that the medical professionals of today and the future require a much broader skill set than just good clinical knowledge and expertise. These additional skills and competencies have been formally articulated by medical societies and organisations, for example the CanMEDS framework outlined by the Royal College of Physicians and Surgeons of Canada1 and the Core Competencies of the Accreditation Council for Postgraduate Medical Education (ACGME)2. Healthcare organisations around the world have reiterated that effective leadership should be present at all levels, whether it is a clinical or academic field3.